2015
DOI: 10.1016/j.cub.2015.08.047
|View full text |Cite
|
Sign up to set email alerts
|

The Nuclear Proteome of a Vertebrate

Abstract: Summary The composition of the nucleoplasm determines the behavior of key processes such as transcription, yet there is still no reliable and quantitative resource of nuclear proteins. Furthermore, it is still unclear how the distinct nuclear and cytoplasmic compositions are maintained. To describe the nuclear proteome quantitatively, we isolated the large nuclei of frog oocytes via microdissection and measured the nucleocytoplasmic partitioning of ~9000 proteins by mass spectrometry. Most proteins localize en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
148
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 51 publications
15
148
0
Order By: Relevance
“…On the other hand, GO terms enriched in the background proteome were mainly associated with functions typical of mitochondrial proteins (Fig 3B). We next compared our results with previous data of nucleocytoplasmic partitioning (Wühr et al , 2015), where each protein was assigned to the RNC (relative nuclear concentration) calculated for over 9,000 proteins of Xenopus laevis (Fig 3C). We found that the NIP shows a significant enrichment of proteins with high RNC values, indicative of asymmetric distribution with higher nuclear concentration.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, GO terms enriched in the background proteome were mainly associated with functions typical of mitochondrial proteins (Fig 3B). We next compared our results with previous data of nucleocytoplasmic partitioning (Wühr et al , 2015), where each protein was assigned to the RNC (relative nuclear concentration) calculated for over 9,000 proteins of Xenopus laevis (Fig 3C). We found that the NIP shows a significant enrichment of proteins with high RNC values, indicative of asymmetric distribution with higher nuclear concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of cargos known from literature for IPO5, KPNB1 (Kimura et al , 2017), and XPO1 (Thakar et al , 2013; Kırlı et al , 2015; Wühr et al , 2015). For XPO1, only cargos significant in at least two out of the three previous large‐scale studies were considered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations